Modernización de la gestión pública y rendición de cuentas: análisis del caso ecuatoriano (Estudios) - Freire Briones, Milton A. (2019)
The goal of this article is to understand why the modernization of public administration contributes to improving the conditions for the rendering of accounts in Ecuador. The research uses the analytical framework for policy design, the process traicing with Bayesian logic, and the approach of a causal mechanism that goes from policy agenda configuration, through the formulation of public policy, the institutional change, the coordination and adaptation of existing institutions to the improvement of accountability conditions. The verification of the causal mechanism shows a confidence of 98.8%, which concludes that in Ecuador there is evidence to affirm that the modernization of public administration had contributed to improving accountability conditions.